Science as a Strategy for Social Work. Issue 2 (4th May 2017) - Blau, Joel
ABSTRACT: For more than one hundred years, various forms of science have been promoted to boost social work's status as a profession. Evidence-based practice and talk about the science of social work are only the most recent manifestations of this pattern. Counter to this trend, this article argues that the latest upsurge of interest in scientific social work is no more likely than any of its predecessors to address the problems of the profession. Beginning with a linguistic analysis of the words science and scientific as positive signifiers, the article traces social work's long history of science talk as a means of reassuring funding agencies and bolstering the profession's status. Drawing on a critique of this discourse as the latest example of abstracted empiricism, it then contends that while scientific social work can only rarely capture what occurs in the field, its attempt to do so actually undercuts practitioners' professional judgment and discretion. Last, after rejecting science talk as counterproductive, the article concludes with recommendations for an alternative strategy that might better position social work to reconcile its advocacy of social justice with its concerns about its professional status.